Penentuan Sun Potection Factor (SPF) Fraksi metanol dan n-Heksan daun kebiul (Caesalpinia Bonduc) Secara In-Vitro - Rahmawati Tri Yuni; Dwi Fitri Yani (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Kebiul leaves (Caesalpinia bonduc) are a part of the plant secondary metabolite compounds that have photoprotective properties so they can absorb ultraviolet light. This study aims to determine the fraction of sunscreen activity methanol and n-hexane of kebiul leaves using the in-vitro method. The kebiul leaves were extracted by the method maceration using methanol and then fractionated with n-hexane. The methanol fraction contains secondary metabolites of flavonoids, tannins, and saponins. The n-hexane fraction contains flavonoids, steroids and terpenoids. The fraction activity is measured absorbance using UV-Vis spectrophotometry. The SPF value generated with concentrations of 200, 400, 600, 800, and 1000 ppm in the methanol fraction, respectively 1,7, 3,81, 5,21, 6,5, and 7,78. Meanwhile, the SPF value for n-hexane fraction was respectively 1.58, 2.82, 4.09, 5.26, and 6.51. The methanol and n-hexane fractions of kebiul leaves can be used as a sunscreen material, at a concentration of 600 ppm, 800 ppm, and 1000 ppm included in the suntan category (moderate to extra protection).